Scaffolding in Mathematics Learning Social Arithmetic Material to Improve Students' Mathematical Thinking - Wedastuti, Ni Ketut; Sunismi, Sunismi; Faradiba, Suryasari (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to describe the scaffolding process in learning social arithmetic to improve students' mathematical thinking skills. The ability to think mathematically is an important skill for students because evaluating information systematically is very useful in solving a problem. This research method uses descriptive research methods with a qualitative approach. This research was conducted in class VII SMP 6 Singosari Malang. The instrument used is Higher Order Thinking Skill (HOTS) questions in social arithmetic math problems. The subjects in this study consisted of two people with high and low levels of mathematical thinking. The results of this study indicate that the scaffolding technique can improve students' mathematical thinking. After receiving scaffolding, Students with high mathematical thinking skills can improve mathematical thinking from the reproduction and connection stages to the analysis stage. In contrast, students with low mathematical abilities can improve mathematical thinking from the reproduction stage to the connection stage after being given scaffolding.